2012
DOI: 10.1089/vbz.2011.0864
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Tick-Borne Infections in Military Working Dogs in the Republic of Korea

Abstract: In this study we endeavored to determine the seroprevalence of tick-borne infections in the military working dog (MWD) population in the Republic of Korea (ROK). Our sample population consisted of 182 serum samples from MWDs for 3 different years (1996, 2002, and 2007). In addition, 63 whole blood samples from 2007 were available for polymerase chain reaction (PCR). Serum samples were evaluated by a commercially available enzyme-linked immunosorbent assay (ELISA) and immunofluorescence assay (IFA) for Ehrlichi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 121 publications
(235 reference statements)
1
17
0
Order By: Relevance
“…B. burgdorferi is the agent of Lyme disease, which occurs globally, and can infect a wide-range of animals including rodents, ruminants, carnivores, and birds, as well as humans. Among samples from 526 pet dogs, 0.38% were serologically positive for Borrelia infection, which correlates with investigations performed in dogs in individual reports in other countries [ 15 , 16 ].Considering the vector's geographical distribution and abundance, it is easy to understand why the rate of positive samples reported here was significantly lower than the 4.5–11% and 1.4–11.6% infection rates reported in dogs in the UK and USA, respectively [ 17 , 18 ]. Lyme disease was first reported in China in 1985 with a seropositivity rate of 1.06∼12.8% in the 30 000 people randomly sampled [ 19 ].…”
Section: Discussionsupporting
confidence: 80%
“…B. burgdorferi is the agent of Lyme disease, which occurs globally, and can infect a wide-range of animals including rodents, ruminants, carnivores, and birds, as well as humans. Among samples from 526 pet dogs, 0.38% were serologically positive for Borrelia infection, which correlates with investigations performed in dogs in individual reports in other countries [ 15 , 16 ].Considering the vector's geographical distribution and abundance, it is easy to understand why the rate of positive samples reported here was significantly lower than the 4.5–11% and 1.4–11.6% infection rates reported in dogs in the UK and USA, respectively [ 17 , 18 ]. Lyme disease was first reported in China in 1985 with a seropositivity rate of 1.06∼12.8% in the 30 000 people randomly sampled [ 19 ].…”
Section: Discussionsupporting
confidence: 80%
“…In a serological study to assess the exposure of MWD to tick-borne pathogens in South Korea, seroprevalence for Anaplasma and Ehrlichia were 4.4 % and 0.6 % based on ELISA, and 24.7 % and 22.5 % based on IFAT, respectively, and 1.1 % for B. burgdorferi ( s.l. ) based only on ELISA [ 23 ]. In Spain (Madrid), out of 131 dogs from the National Police Department, 2.3 % had antibodies to E. canis [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Without any clinical signs, the prevalence in horses was less than 6.7% (Tables 6–8). Furthermore, several case reports and case series have been published on domestic animals in North America (e.g., Cockwill et al, 2009; Granick et al, 2009; Uehlinger et al, 2011), and serological studies have shown a wide evidence of dogs, cats, and horses being in contact with A. phagocytophilum in USA, Canada, and Asia (e.g., Magnarelli et al, 2001; Billeter et al, 2007; Bowman et al, 2009; Villeneuve et al, 2011; Bell et al, 2012; Ybañez et al, 2012). Additionally, serological and molecular evidence have been provided from North Africa (which also is an endemic area for I. ricinus ) that horses and dogs become infected with A. phagocytophilum (M'Ghirbi et al, 2009, 2012).…”
Section: Hosts and Reservoirsmentioning
confidence: 99%